Gestão da manutenção de edificações com o BIM : enfoque nas manifestações patológicas de elementos de construção - Santos, Karine de Paula Bastos (2017)
The operational and maintenance phase is the longest and most expensive lifecycle period of buildings, compared to design and construction phases. Appropriate maintenance planning ensures cost reductions and the compliance of building performance requirements. The use of Building Information Modeling has rapidly increased in Architecture, Engineering and Construction Industry (AEC), especially in the design and construction phases. Additionally, BIM can be implemented during the operational and maintenance phases. BIM technology enables the building graphical representation using 3D virtual models linked to a lot of data and construction process information, technical specifications, building materials features, among others. Despite its potential for maintenance management of existing buildings, there are not many studies on BIM support in the diagnosis of construction damage, analysis of root causes and repair methods. This work aims at proposing a methodology to help building maintenance management through BIM platform, more specifically focusing on construction damage. Three Autodesk BIM software were used for data collections: (1) Revit® to create 3D models from architectural, MEP and structural designs; (2) BIM 360 Glue® to export models and (3) BIM 360 Field® to link the models to building documents and technical materials about construction damage, diagnosis and repair methods. The results showed that BIM represents an effective support tool to enhance maintenance management quality and construction systems performance, which in turn are vital to reduce deterioration processes, rehabilitation costs and to extend building service life.